Australian green roofs attract bees with similar functional traits, but species-specific responses to local attributes differ significantly - J. Schiller; J. Brown; A.K. Hahs; N.S.G. Williams; C.G. Threlfall (Basic and Applied Ecology, 2025)
Bees are important pollinators but are globally in decline due to the effects of climate and land use change, for example loss of habitat and urban heat island associated with urbanisation. Green roofs can provide resources and habitat for urban bees. However, it is unclear how the attributes of green roofs influence their habitat value. To better understand the biodiversity value of green roofs, it is crucial to understand what type of green roofs best support native bees and the attributes that affect this. A mix of active and passive sampling methods were used to survey bees from 20 green roofs in Melbourne during summer 2019/20. Local and landscape attributes of the green roofs were collected in the field or via spatial analysis using GIS. A total of 20 bee species utilising green roofs were identified. Generalised linear models (GLM) and hierarchical modelling of species communities (HMSC) found that impervious ground cover within the surrounding landscape was a strong negative predictor for bee abundance and richness. Further, increased foraging resources on the green roofs had positive effects on bee abundance and richness. Height above ground had a negative effect on some bee species, but their body size was not an influencing factor. These findings are important for green roof planting design and suggest that roofs lower in height that contain a diversity of floral resources are most suited to support diverse native bee communities.